Experimental investigation on ultrasonic vibrational drilling of carbon fiber reinforced polymer laminates - Chui, Yan Li. (2009)
This report explores the novel concept of ultrasonic vibrational drilling of uni-directional carbon fiber reinforced polymer (CFRP) composite laminates. Three customized drill bits namely Dagger, Reamer and Router are used to perform the hole drilling experiments with two different feed rates and two rotational drill speeds.